Enhancing the Halal Agri-Food Sector: Harnessing Blockchain for Opportunity and Innovation - Azmar, Zahirah; Syarifah, Ramzani Lutfi; Zahran, Hasna Imaratuz; Dzaki, Muhammad Faza; Cahyadi, Eko Ruddy (Halal Studies and Society, 2024)
The halal industry is seeing significant growth, driven by heightened consumption and awareness among Muslims, resulting in a rising demand for high-quality products. The halal agri-food sector is a very promising industry that garners significant customer interest regarding the quality and safety of its products. Nevertheless, the halal agri-food sector is presently encountering considerable hurdles in guaranteeing product authenticity and sustainability, especially in combating fraud, overseeing supply sources, and upholding standards across various locations. Furthermore, recent advancements in technologies like blockchain have garnered substantial interest as a solution for urgent challenges, and their integration could markedly improve procedures and yield benefits for the halal agri-food sector. This study sought to examine the existing literature regarding the potential and challenges of blockchain technology in the halal agri-food sector through a qualitative methodology. The results indicated that blockchain enhanced traceability, increased supply chain efficiency, and supported Sustainable Development Goals 9 and 12. The findings of this study indicate that blockchain integration enhanced the global halal market by optimizing production processes and bolstering consumer confidence, hence propelling the halal agri-food sector to emerge as one of the most profitable and reputable industries worldwide.